‘Everything is different’: the impact of acquiring aphasia on information seeking - Kvikne, Birgit; Berget, Gerd (Information Research an international electronic journal, 2024)
Introduction. Aphasia is a language impairment that can lead to significant changes in all aspects of life, including information-seeking behaviour. This paper presents findings from a qualitative study exploring how acquiring aphasia impacts information seeking. The study also assesses the applicability of the information behaviour theory of transitions as a framework to explore and understand this life change in the context of information-seeking behaviour. Method. Data were collected through semi-structured interviews and observation of search behaviour of 20 people diagnosed with aphasia. Analysis. Interviews were recorded, transcribed, anonymised and imported into NVivo. The data were examined using thematic analysis. Results. The study found that acquiring aphasia entails significant changes, necessitating the development of new information-seeking behaviour. The findings suggest that creating more inclusive information systems for people with aphasia is possible, with features such as support for word mobilisation and tolerance for spelling errors. Conclusions. Acquiring aphasia led to significant changes in information seeking behaviour. The information behaviour theory of transitions proved useful in identifying information seeking barriers for people with aphasia, as well as providing knowledge on how to support information-seeking behaviour for this cohort.